Importance of family coexistence for the health of the elderly adult in retirement and / or asylum houses (Revista de Investigaciones Universidad del Quindío, 2021)
This article addresses the study of the consequences and damages that are generated in older adults caused by abandonment and lack of coexistence with their relatives, particularly the case of those who are admitted to retirement homes or also called asylums. The emotional and psychological deterioration suffered by the fragile or null relationship with relatives triggers a series of negative events such as lack of appetite, depression, isolation, refusal to carry out group activities or those inherent to their optimal motor skills. This series of events leads them to present pathologies that end up ending their life in the short term. However, the aforementioned negative events can be canceled through the implementation of restorative circles, in which older adults have the opportunity to express their feelings and emotions in a free, spontaneous and respectful way, which encourages them a better communication and relationship with family members. Strengthening with this, the reinforcement of affective ties, the emotional improvement and health of the elderly.
Keywords: Elderly; retired people center; restorative circle